Echocardiographic examination of mitral valve abnormalities in the paediatric population: current practices. (8th January 2020) - Cantinotti, Massimiliano; Giordano, Raffaele; Koestenberger, Martin; Voges, Inga; Santoro, Giuseppe; Franchi, Eliana; Assanta, Nadia; Valverde, Israel; Simpson, John; Kutty, Shelby
Abstract: We reviewed the recent literature for echocardiographic assessment of mitral valve abnormalities in children. A literature search was performed within the National Library of Medicine using the keywords "mitral regurgitation and/or stenosis, children." The search was refined by adding the keywords "echocardiographic definition, classification, and evaluation." Thirty-one studies were finally included. Significant advances in echocardiographic imaging of mitral valve defects, mainly due to the implementation of three-dimensional technology, contribute to a better understanding of the underlying anatomy. However, heterogeneity between classification systems of mitral valve disease severity is a serious problem. For regurgitant lesions, there is only very limited evidence from small studies that support the adoption of quantitative/semi-quantitative indexes commonly employed in adults. Despite the lack of evidence base, qualitative evaluation of regurgitation severity is often employed. For stenotic lesions, no clear categorisation based on trans-valvular echocardiography-derived "gradients" has been consistently applied to define mild, moderate, or severe obstruction across different paediatric age ranges. Quantitative parameters such as valve area have also been poorly validated in children. Adult recommendations are frequently applied without validation for the paediatric age. In conclusion, significant advances in the anatomical evaluation of mitral valve diseases have been made, thanks to three-dimensional echocardiography; however, limitations remain in the quantitative/semi-quantitative estimation of disease severity, both with respect to valvular regurgitation and stenosis. Because adult echocardiographic recommendations should not be simply translated to the paediatric age, more specific paediatric guidelines and standards for the assessment of mitral valve diseases are needed.